2011
DOI: 10.1073/pnas.1109680108
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for long-term memory formation when synaptic strengthening is impaired

Abstract: Long-term memory (LTM) formation has been linked with functional strengthening of existing synapses and other processes including de novo synaptogenesis. However, it is unclear whether synaptogenesis can contribute to LTM formation. Here, using α-calcium/calmodulin kinase II autophosphorylation-deficient (T286A) mutants, we demonstrate that when functional strengthening is severely impaired, contextual LTM formation is linked with traininginduced PSD95 up-regulation followed by persistent generation of multiin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 34 publications
3
77
0
Order By: Relevance
“…Forebrain-restricted expression of a dominant-negative form of PAK impairs contextual fear LTM (Hayashi et al 2004). In these mutants basal synapse numbers are normal in the hippocampus (Hayashi et al 2004), but the authors did not test whether conditioning-induced synaptogenesis is impaired (compare with, Radwanska et al 2011).…”
Section: Fyn and Other Kinasesmentioning
confidence: 99%
“…Forebrain-restricted expression of a dominant-negative form of PAK impairs contextual fear LTM (Hayashi et al 2004). In these mutants basal synapse numbers are normal in the hippocampus (Hayashi et al 2004), but the authors did not test whether conditioning-induced synaptogenesis is impaired (compare with, Radwanska et al 2011).…”
Section: Fyn and Other Kinasesmentioning
confidence: 99%
“…Specific LTP can be induced in T286A mice in the presence of rapamycin In T286A mice, immediate learning was impaired, but when the task was repeated in a massed training protocol of fear conditioning, learning occurred (Irvine et al 2005). Radwanska et al (2011) showed that this learning could be impaired by rapamycin.…”
Section: Increasing Camp Concentration Induces An Ltp Which Is Indepementioning
confidence: 99%
“…Specific LTP can be induced in T286A mice in the presence of rapamycin In T286A mice, immediate learning was impaired, but when the task was repeated in a massed training protocol of fear conditioning, learning occurred (Irvine et al 2005). Radwanska et al (2011) showed that this learning could be impaired by rapamycin.We thus studied the effect of rapamycin on the LTP induced by four trains in mutant mice after a recovery period in submersion. Surprisingly, instead of inhibiting LTP, the incubation of slices with rapamycin increased the potentiation level of the stimulated pathway (Fig.…”
mentioning
confidence: 99%
“…These LTP impairments were demonstrated in hippocampal slices and in anaesthetised mice. However, despite the absence of NMDA (Irvine, Vernon, & Giese, 2005;Irvine et al, 2011;Radwanska et al, 2011). This was shown after training in contextual fear conditioning and the passive avoidance task.…”
Section: The Acamkii T286a Mouse Modelmentioning
confidence: 73%
“…aCaMKII T286A mice have a targeted point mutation in the aCaMKII gene that prevents phosphorylation at the autonomy site threonine-286 (Giese, Fedorov, Filipkowski, & Silva, 1998). Thorough electrophysiological investigation have established that the lack of T286 autophosphorylation completely abolishes NMDA receptor-dependent LTP at hippocampal CA1 synapses in adult, but not at neonatal age (Cooke et al, 2006;Giese et al, 1998;Irvine et al, 2011;Radwanska et al, 2011;Villers, Giese, & Ris, 2014;Yasuda, Barth, Stellwagen, & Malenka, 2003). These LTP impairments were demonstrated in hippocampal slices and in anaesthetised mice.…”
Section: The Acamkii T286a Mouse Modelmentioning
confidence: 94%